Observational cohort study of outcomes in patients admitted to the intensive care unit for acute exacerbation of chronic obstructive pulmonary disease. Issue 8 (7th August 2018) - Sivakumar, Sivanth; McNally, Angus; Tobin, Jonathan; Williamson, Jonathan; Aneman, Anders
Abstract: Background: Patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) are often referred to the intensive care unit (ICU) for non‐invasive respiratory support. Aims: To describe the characteristics of patients with AECOPD admitted to ICU focusing on the performance of ICU prognostic systems, decisions to limit medical therapy and mortality outcomes. Methods: Retrospective review of patients admitted between 2009 and 2016, separately in patients with active treatment and limitation or withdrawal of medical therapy. ICU acuity scores, blood gas analyses and ICU, in‐hospital and 1‐year mortality were analysed using descriptive statistics and logistic regression. Results: A total of 403 patients was studied with an overall ICU mortality of 6.4%. The predicted risk of death in hospital using ICU scoring systems was 19% compared to the observed mortality of 15%. One‐year mortality was 34%. Patients with limitation of medical therapy represented 32% of the total cohort and had higher mortality in ICU (13%), in hospital (30%) and at 1‐year follow up (53%). Withdrawal of life‐sustaining therapy occurred in 4% of patients who all died in ICU. Decreased arterial oxygenation and bicarbonate concentration as well as increased arterial carbon dioxide levels were overall associated with an increased likelihood of in‐hospital mortality but no independent predictors of 1‐year mortality were identified. Conclusion: In patients admitted to ICU for AECOPD, limitations of medical therapy are frequent and associated with significant mortality. Involving palliative care in addition to respiratory physicians and intensivists in the management of AECOPD patients admitted to ICU needs to be explored further.